Metal-on-metal hip resurfacing: a consensus from the Advanced Hip Resurfacing Course, Ghent, June 2009. - De Smet, K; Campbell, P; Gill, H (2010)
We report the consensus of surgical opinions of an international faculty of expert metal-on-metal hip resurfacing surgeons, with a combined experience of over 18,000 cases, covering required experience, indications, surgical technique, rehabilitation and the management of problematic cases.